Case report: Trans-papillary free stenting of the cystic duct and of the common bile duct in a double biliary ducts anastomoses of a right lobe living donor transplantation - Salvatore Gruttadauria (BMC Surgery, 2021)
Abstract Background One of the major issues related to the living donor liver transplantation recipient outcome is still the high rate of biliary complication, especially when multiple biliary ducts are present and multiple anastomoses have to be performed. Case presentation and conclusion We report a case of adult-to-adult right lobe living donor liver transplantation performed for a recipient affected by alcohol-related cirrhosis with MELD score of 17. End-stage liver disease was complicated by refractory ascites, portal hypertension, small esophageal varices and portal gastropathy, hypersplenism, and abundant right pleural effusion. Here in the attached video we described the adult-to-adult LDLT procedures, where a right lobe with two biliary ducts draining respectively the right anterior and the right posterior segments has been transplanted. LDLT required a biliary reconstruction using the native cystic and common bile ducts stented trans-papillary with two 5- French 6 cm long soft silastic catheter. None major complications were detected during post-operative clinical courses. Actually, the donor and the recipient are alive and well. The technique we describe in the video, allow to keep the biliary anastomoses protected and patent without having the risk of creating cholestasis and the need of invasive additional procedure. No living donor right lobe transplantation should be refused because of the presence of multiple biliary ducts.